Why do some people with type 2 diabetes who are using insulin have poor glycaemic control? A qualitative study - Tong, W.T.; Vethakkan, S.R.; Ng, C.J. (BMJ Publishing Group, 2015)
Objective: To explore factors influencing poor glycaemic control in people with type 2 diabetes using insulin. Research design: A qualitative method comprising indepth individual interviews. A semistructured interview guide was used. The interviews were audiorecorded, transcribed verbatim and analysed using a thematic approach. Participants: Seventeen people with type 2 diabetes using insulin with glycated haemoglobin (HbA1c) ≥9% for >1 year. Setting: The Primary Care Clinic and Diabetes Clinic in the University of Malaya Medical Centre (UMMC), Malaysia. Results: Data analysis uncovered four themes: lifestyle challenges in adhering to medical recommendations; psychosocial and emotional hurdles; treatment-related factors; lack of knowledge about and self-efficacy in diabetes self-care. Conclusions: Factors that explain the poor glycaemic control in people with type 2 diabetes using insulin were identified. Healthcare providers could use these findings to address patients' concerns during consultations and help to improve glycaemic control.